Empirical models challenging biblical criticism - Person, Raymond F., Jr., 1961-; Rezetko, Robert (Atlanta : SBL Press, 2016)
"Empirical models based on ancient Near Eastern literature and variations between different textual traditions have been used to lend credibility to the identification of the sources behind biblical literature and the different editorial layers. In this volume, empirical models are used to critique the exaggerated results of identifying sources and editorial layers by demonstrating that, even though much of ancient literature had such complex literary histories, our methods are often inadequate for the task of precisely identifying sources and editorial layers"--
Limited Efficacy in Reconstructing the Gospel Sources for Matthew and Luke Bibliography; Contributors; Ancient Sources Index; Modern Authors Index
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Bible -- Criticism, Redaction -- History; Bible; Classical literature -- History and criticism; Classical literature; RELIGION / Biblical Studies / Exegesis & Hermeneutics; Criticism, interpretation, etc; History; Electronic books